Kinetics and mechanism of the electrochemical reduction of molecular oxygen on platinum in KOH: influence of preferred crystallographic orientation - Zinola Sánchez, Carlos Fernando (1994)
The oxygen electroreduction reaction has been studied at both preferred oriented and conventional polycrystalline platinum rotating disc electrodes in x m KOH (0.05 ⩽ x ⩽ 3.0) aqueous solutions under oxygen saturation at 25°C. At low current densities, Tafel lines with slope -0.060 V decade⁻¹ have been obtained at all platinum electrodes. At high current densities, higher Tafel slopes ranging from -0.18 to -0.40 V decade⁻¹ have been observed, depending on the type of preferred oriented Pt and KOH concentration. Rotating ring-disc electrode data have shown that a higher amount of H₂O₂ is produced on one type of preferred oriented surface at all KOH concentrations. A complex reaction scheme has been used to evaluate the electrochemical rate constants of the reaction steps at three platinum electrodes.